Pengelolaan Program Pemanduan Bakat Olahraga Pada Pusat Pembinaan Dan Latihan Pelajar Provinsi Bengkulu - Azwandi (Manajer Pendididikan, 2024)
The aim of this research is to analyze the management of the sports coaching program at the student development and training center in Bengkulu province. The method used uses qualitative research. Data collection techniques use interview sheets, observation sheets, and document analysis. The research results show that planning has been carried out by the management of the sports talent scouting program and still needs improvement. program implementation does not comply with plans such as training schedules, selection of athletes, and availability of infrastructure. The evaluation carried out by PPLP Bengkulu Province was less structured, did not have adequate documentation and did not have a regular schedule. The follow-up carried out did not have thorough planning and was not optimal because there were some who had no follow-up after carrying out the evaluation.